2017
DOI: 10.4067/s0717-95022017000200046
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hypoglycemic Effects of Momordica cochinchinensis Spreng: (Gac) Aril Extract on Reproductive Damages in Streptozotocin (STZ)-Induced Hyperglycemia Mice

Abstract: SUMMARY:The aim of present study was to investigate the effect of Momordica cochinchinensis (Gag) aril (GA) aqueous extract on male reproductive system of streptozotocin (STZ)-induced hyperglycemia (HG) mice. GA were extracted with distilled water (DW) and analyzed for in vitro antioxidant capacities. ICR male mice were divided into 7 groups: 1) control, 2) DW, 3) GA 1000 mg/kg BW, 4) HG, 5) HG + glibenclamide, 6 and 7) HG + GA 500 and 1000 mg/kg BW respectively (7 mice/ group). In HG groups, mice were induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Previous studies have reported that DM can cause histological alterations and significant reductions in seminal weight (Sampannang et al, 2017;Tsounapi et al, 2017), which is consistent with the results of this study. These changes have been found to inhibit the ability to produce or secrete seminal fluid (Tsounapi et al, 2017), a finding that is corroborated by the changes in seminal epithelial morphology and height shown in Figures 1-3.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previous studies have reported that DM can cause histological alterations and significant reductions in seminal weight (Sampannang et al, 2017;Tsounapi et al, 2017), which is consistent with the results of this study. These changes have been found to inhibit the ability to produce or secrete seminal fluid (Tsounapi et al, 2017), a finding that is corroborated by the changes in seminal epithelial morphology and height shown in Figures 1-3.…”
Section: Discussionsupporting
confidence: 94%
“…Protein phosphorylation is a post-translational process of most cellular modifications including sperm physiological capacitation and acrosome exocytosis (Salicioni et al, 2007;Shivaji et al, 2007;Stival et al, 2016). Tyrosine-phosphorylated proteins are specifically localised within testicular tissue (Arad-Dann, Beller, Haimovitch, Gavrieli, & Ben-Sasson, 1993;Chaichun et al, 2017) and are assumed to play a role in spermatogenesis (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, 2016;Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, 2016;Iamsaard et al, 2014;Sampannang et al, 2017Sampannang et al, , 2018 2013; Talat et al, 2016). Thus, monitoring for significant increases in OPN may help to predict microvascular diabetes complications (Talat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that mimosine may have a major function as anti-cell proliferation of male germ cells since previous reports have demonstrated in other system about theinhibitory activities of many cancer cells, cell divisions, cell proliferations and differentiations, herbicidal, insecticide, and nematicide activities (Tawada, 1990;Wang et al;Hughes & Cook;Krude;Chung et al;Park et al;Bottini-Luzardo et al;Fallon;Nguyen & Tawata). Similar to others, the testicular histopathology, such as atrophic and germ cell degenerating seminiferous tubules, damaged by mimosine in this study was also comparable to other anti-cellular division drug demonstrated previously (Iamsaard et al, 2014;Sukhorum et al, 2016;Iamsaard et al, 2017a,b;Sampannang et al, 2017). In conclusion, the acute consumption of LL containing high mimosine levels must be avoided to protect the reproductive impairment in men.…”
Section: Discussionsupporting
confidence: 90%
“…These proteins have also been found to be localised in Leydig cells, Sertoli cells, spermatogonia, spermatocytes and spermatids, which are assumed to be important for spermatogenesis and androgen synthesis (Chaichun, Arun, Burawat, Kanla, & Iamsaard, ). The presence of TyrPho proteins in rat epididymal tissue and fluid has also been investigated (Sawatpanich et al, ), and improvements in testicular TyrPho protein changes have been associated with normal sperm and testosterone production (Burawat, Uabundit, Arun, Nualkaew, & Iamsaard, ; Iamsaard et al, , ; Iamsaard, Sukhorum, Sampannang, et al, ; Maneenin et al, ; Sampannang et al, ). Changes in TyrPho protein expression in the testis have been associated with stress‐related and diabetic conditions (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, ; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, ; Sampannang, Arun, Burawat, Sukhorum, & Iamsaard, ; Sampannang et al, ).…”
Section: Introductionmentioning
confidence: 99%